Problems in Physics Aimed at Biology: A Contribution to the Initial Formation of the Teacher through the Complexity in Problems Proposed by Halliday Volume II (Global Journal of Human-Social Science, 2023)
This article presents an excerpt from dissertation research on initial teacher education that analyzed and identified the relationships of the complexity involved in solving problems proposed by Halliday - volume II by 26 undergraduate students in Biology from a Public University in the State of Paran Therefore the action research methodology was used for the collection and development of the research associated with the Grounded Theory methodology for data analysis followed by the moments of open axial and selective coding The problem that this research solved was What is the influence of complex Physics problems on the learning process of Biology undergraduate students In this way the complex relationships built within the training process of the future Biology teacher and their influence on the teaching-learning process were identified The main results show that the formation process of such students future teachers reflects the concept of complexity and that a formative process with problembased learning enables the understanding of physical concepts on the subject of fluids in volume II of Halliday
Keywords: complex problems; physics teaching; biology teacher formation